En ny hypostas? En kritisk granskning av den mänskliga hypostasen i Zizioulas teologiska personalism - Hermansson,Daniel (2023)
The Greek-orthodox theologian John Zizioulas has been thoroughly studied, and both appreciated and criticized for his theological personalism. His understanding of the human person after the fall sees her personhood as damaged and imperfect. She is in many was an isolated individual, bound to her mortal nature and in dire need of salvation. Through baptism, she obtains a “new hypostasis” and a “new identity on the level of personhood”. But does this not imply a discontinuation as regards to personal identity, so that we cannot speak of the same person before and after baptism? What then of the personalist thrust of Zizioulas theology? In this essay I criticize Zizioulas account of the human hypostasis, mainly his idea of a “new hypostasis” through baptism, and suggest that a key to a better theological account lies in Maximus the Confessor’s distinction of logos and tropos for the human hypostasis. I also suggest that every hypostasis of every nature has the ability to become persons in the modern sense through divinization, without the need to become “new” hypostases.
Keywords: Zizioulas; theological personalism; hypostasis; Maximus Confessor; logos; tropos.